Pengaruh Kualitas Produk, Citra Merek dan Promosi Terhadap Minat Beli Iphone (Studi Pada Mahasiswa Di Kota Malang) - Abdur Rahman; Agus Widarko; Eka Farida (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of product quality, brand image and promotion on iPhone buying interest. This research uses a study on student consumers in the city of Malang, the data obtained by distributing questionnaires to students of Brawijaya University, Islamic University of Malang and Muhammadiyah University of Malang selected by purposive sampling. Determination of the number of samples using the Slovin formula and the results obtained were 75 respondents. The analytical method used in this study is the research instrument test (validity test, reliability test), normality test, classical assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis test (F test, t test) and coefficient test determination of data processing using SPSS 25. The results of this study indicate that product quality, brand image and promotion simultaneously affect buying interest in iphone. Partially, product quality has a significant effect on buying interest in iPhone, while brand image and promotion partially have no significant effect on buying interest in iPhone. Keywords: Product Quality, Brand Image, and Promotion.